1984
DOI: 10.1063/1.447612
|View full text |Cite
|
Sign up to set email alerts
|

EPR of Mn2+ in polycrystalline dolomite

Abstract: The EPR spectrum at 9.1 GHz of the M = l/2~-l/2 transition for Mn2+ in polycrystalline dolomite has been studied using a detailed computer simulation of the line shapes in the powder pattern spectrum. The accuracy of the analytical procedure was verified for the spectrum of Mn2+ in calcite, yielding magnetic constants which were in excellent agreement with previous polycrystalline and single crystal results. The EPR parameters obtained for Mn2+ in dolomite are g = 2.0020(2), A = -9.48(2) mT for Mn 2 + substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
2

Year Published

1988
1988
2006
2006

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 15 publications
1
29
1
2
Order By: Relevance
“…1,10,15,20 -23,25,27,30 The values of D 0 range between 79.5 and 80.5 G with a mean value of 79.95 G, quite comparable with those present in literature. 1,10,20,21,25,27,30 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,10,15,20 -23,25,27,30 The values of D 0 range between 79.5 and 80.5 G with a mean value of 79.95 G, quite comparable with those present in literature. 1,10,20,21,25,27,30 …”
Section: Discussionmentioning
confidence: 99%
“…The position of the transitions depends on the linewidth and the lineshape. According to the previous simulations, 20,21,30 we consider a Lorentzian absorption function with a half-width  of 1 G.…”
Section: Magnetic Parameters Of Mn 2+ Ion In Calcitementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, using the values of the 13 C and 18 O isotope shifts, it has been possible to reassemble Greek stelae and identify incorrectly associated fragments (14). However, later work has shown that the variability of the isotope shifts within a marble block is usually a substantial fraction of the all-quarry variability, making fragments association extremely uncertain (15,16).…”
Section: Introductionmentioning
confidence: 94%
“…4). The other structure is a double sextet (between 320 and 370 mT) arising from isolated Mn 2+ in TiO 2 [14]. a) b) This signal is not very much affected by the thermal annealing.…”
mentioning
confidence: 95%